Barriers to alcohol intervention program: A scoping review - Selly Jaimon; Richard Avoi; Mohd Nazri Bin Mohd Daud; Pravina Deligannu; Zulkhairul Naim Bin Sidek Ahmad (The Korean Academy of Family Medicine, 2025)
Excess alcohol intake is associated with many negative effects and is a major cause of mortality and morbidity worldwide. World Health Organization has established a global plan with 10 primary policy areas and interventions and six important action areas to reduce alcohol’s negative effects. However, alcohol intervention programs face several challenges that can hinder their success in assisting patients with alcohol consumption reduction and cessation. The objective of this scoping review was to identify the barriers to the implementation of alcohol intervention programs. The Joanna Briggs Institute recommendations and PCC (participants, concepts, context) eligibility criteria were used for the review. A combination of search phrases was used to narrow the literature search to 2014–2024 English-language papers and original research articles with full access. After removing duplication, 3,846 articles remained from the 5,128 found. After further exclusions, 19 eligible studies were included in this review. Five main barriers to care were identified: service-level barriers, barriers to care seeking, stigma, socio-cultural barriers, and external barriers. Robust regulations and implementation are necessary to effectively address service levels and external barriers. To enhance help-seeking behaviors, alcohol screening should be implemented, strict management policies for alcohol use disorders should be enforced, and accessible alternatives should be provided. Additionally, public health initiatives should focus on changing societal perceptions to counteract alcohol normalization. These efforts must involve both communities and workplaces.